2016
DOI: 10.1111/sjop.12266
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and trait emotional intelligence in adolescence

Abstract: The existence of individual differences in trait emotional intelligence (trait EI) makes the investigation of factors that contribute to such variations critical. Given the paucity of research in this area, the purpose of this study was the examination of the relationship between parenting styles and trait EI in an adolescent population. The sample of our study consisted of 127 adolescents (M age = 16.4, SD = 0.96; 42.2% female) from Greek schools, 15–19 years old, who were asked to complete questionnaires of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 75 publications
6
30
0
7
Order By: Relevance
“…Our findings also indicate an association of reappraisal with authoritative parenting, as expected (Karim et al, ). Although research into the association between parenting styles and emotion regulation is scarce, evidence from the field of emotional intelligence consistently supports the connection between the experience of authoritative parenting and the application of functional emotion regulation (see Argyriou, Bakoyannis, & Tantaros, , for an analysis). Authoritative parenting is characterized by the encouragement of independence and self‐regulation of children and at the same time being emotionally available as parents (Grolnick & Pomerantz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also indicate an association of reappraisal with authoritative parenting, as expected (Karim et al, ). Although research into the association between parenting styles and emotion regulation is scarce, evidence from the field of emotional intelligence consistently supports the connection between the experience of authoritative parenting and the application of functional emotion regulation (see Argyriou, Bakoyannis, & Tantaros, , for an analysis). Authoritative parenting is characterized by the encouragement of independence and self‐regulation of children and at the same time being emotionally available as parents (Grolnick & Pomerantz, ).…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio se ha considerado oportuno centrarse en los factores de contexto ya que estos aluden a las situaciones sociales, culturales y económicas que posee un alumno y que están relacionados con su ámbito social y familiar (Argyriou, Bakoyannis & Tantaros, 2016). Comprenden el nivel cultural y socioeconómico de los escolares de manera propia, las peculiaridades de su ambiente familiar y, por último, el lugar de residencia en el que habitan (Jaimes, 2016).…”
Section: Factores Contextualesunclassified
“…Nastasa and Sala () showed that democratic parental style positively correlated with emotional intelligence, while dictatorial parent style negatively correlated with trait EI. Argyriou, Bakoyannis, and Tantaros () found that authoritativeness, and marginally authoritarianism, was associated with trait EI in a sample of Greek adolescents. Furthermore, Lim, You, and Ha () showed that maternal emotional support had a significant impact on the EI of Korean high school students.…”
Section: Introductionmentioning
confidence: 99%